(untitled) (KULT_online, 2020)
In Intersectionality as Critical Social Theory Patricia Hill Collins explores intersectionality’s potential to become a critical social theory. Collins asserts that in order for intersectionality to develop fully as a critical social theory, its scholars and practitioners have to profoundly engage with its methodologies, epistemologies, and the activist works upon which it is based. Collin’s monograph can be seen as a dialogical engagement of intersectionality with other theoretical schools of thought and furthers its development into a theory of its own.